2008
DOI: 10.1007/s12325-008-0087-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of beta-blockers on sleep in patients with mild hypertension: a randomized trial between nebivolol and metoprolol

Abstract: Nebivolol was associated with improved sleep (as assessed by the PSQI), whereas metoprolol was associated with a worsening of sleep characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 18 publications
0
23
0
2
Order By: Relevance
“…This study also showed that carvedilol slightly decreased quality of life, whereas nebivolol and bisoprolol had no influence, suggesting that different β-blockers exert different clinically relevant effects. In agreement with this, data from a prospective, randomized, open-label study on the impact of β-blockers on sleep in patients with mild hypertension indicate significant differences between nebivolol versus metoprolol 86. Eligible patients were administered the Pittsburgh Sleep Quality Index questionnaire by a blinded interviewer and were randomized to receive metoprolol or nebivolol.…”
Section: Patient-focused Perspectivesmentioning
confidence: 72%
“…This study also showed that carvedilol slightly decreased quality of life, whereas nebivolol and bisoprolol had no influence, suggesting that different β-blockers exert different clinically relevant effects. In agreement with this, data from a prospective, randomized, open-label study on the impact of β-blockers on sleep in patients with mild hypertension indicate significant differences between nebivolol versus metoprolol 86. Eligible patients were administered the Pittsburgh Sleep Quality Index questionnaire by a blinded interviewer and were randomized to receive metoprolol or nebivolol.…”
Section: Patient-focused Perspectivesmentioning
confidence: 72%
“…The effects of beta-blockers on sleep are not equivocal. A previous study showed that the use of beta-blockers could positively or negatively affect sleep [22]. A case report by Cicolin et al suggested that ACE inhibitors may contribute to OSA by inducing upper airway inflammation [23].…”
Section: Discussionmentioning
confidence: 99%
“…More patients with HCM used antidepressants and β-blockers than the controls. These two drugs have been associated with sleep disturbances and may have influenced the sleep quality of patients with HCM [33,34]. However, multiple regression analysis showed no independent association between medications and sleep quality.…”
Section: Discussionmentioning
confidence: 99%